Counteracting methicillin resistant Staphylococcus aureus through novel Citral-Azithromycin combination - Hitesh K. Sharma; Ibha Singh; Amarnath Karna; Puneet Gupta; Taru Singh; Anoop Kumar; Deepti Pandita; Monalisa Mukherjee; Virinder S. Parmar; Pallavi Agarwal; Viney Lather (Scientific Reports)
Abstract Methicillin-resistant Staphylococcus aureus (MRSA) poses a significant challenge, necessitating novel therapeutic strategies. This study demonstrates the synergistic bactericidal activity of citral, a phytochemical, and azithromycin against clinical MRSA isolates. Checkerboard assays confirmed synergy with a fractional inhibitory concentration index (FICI) of 0.093, while time-kill kinetics showed a reduction in bacterial viability from 5.39 to 2.94 log10 CFU/ml, outperforming monotherapy. Scanning electron microscopy revealed severe cellular damage, indicative of membrane disruption and protein leakage. Notably, the combination extended post-antibiotic effects (PAE) by 4.26 h at MIC, suggesting prolonged antibacterial action. Cytotoxicity assays on normal human fibroblasts demonstrated 93.7% viability at the combined MIC, underscoring its biocompatibility. These findings highlight citral-azithromycin synergy as a promising strategy to enhance antibiotic efficacy against MRSA while minimizing cytotoxicity, supporting the potential of phytochemical-adjuvant combinations in combating antimicrobial resistance.